KNOWLEDGE AND AWARENESS OF CATOPTROPHOBIA AMONG UNDERGRADUATE DENTAL STUDENTS IN CHENNAI- A QUESTIONNAIRE SURVEY - Faaizah Fathima, Dhanraj M. Ganapathy, L. Keerthi Sasanka (Drugs and Cell Therapies in Hematology, 2021)
INTRODUCTION Phobia is a fear or aversion to something.People who suffer from phobia may experience a deep sense of dread or panic when they encounter the source of their fear.Around 19 million Americans have different phobias.It can be of different types like Arachnophobia,Acrophobia,Trypanophobia,Catoptrophobia etc.The most common symptom of a phobia is a panic attack and the other symptoms include chest pain,tightness,choking sensation and many others..The fear of mirrors is generally known as eisoptrophobia or catoptrophobia.People having this phobia are mostly scared of the reflections within.People having phobias can be treated by using therapeutic techniques,medications,or both. AIM To determine the prevalence and knowledge of catoptrophobia among dental students. METHODS AND MATERIALS This study was done in a private dental institution with a sample size of 100. Google forms were made and circulated.The responses were transferred to spss software and the results were obtained. RESULTS The results clearly showed that most of the students were unaware of catoptrophobia and had very little knowledge of this particular phobia. CONCLUSION This research survey concludes that very few people have catoptrophobia and very few are aware of this phobia.More studies should be done in the future to make them more aware.